Chitayat-Hall and Schaaf-Yang syndromes:a common aetiology: expanding the phenotype of MAGEL2-related disorders. Issue 5 (29th March 2018) - Jobling, Rebekah; Stavropoulos, Dimitri James; Marshall, Christian R; Cytrynbaum, Cheryl; Axford, Michelle M; Londero, Vanessa; Moalem, Sharon; Orr, Jennifer; Rossignol, Francis; Lopes, Fatima Daniela; Gauthier, Julie; Alos, Nathalie; et al.
Abstract : Background: Chitayat-Hall syndrome, initially described in 1990, is a rare condition characterised by distal arthrogryposis, intellectual disability, dysmorphic features and hypopituitarism, in particular growth hormone deficiency. The genetic aetiology has not been identified. Methods and results: We identified three unrelated families with a total of six affected patients with the clinical manifestations of Chitayat-Hall syndrome. Through whole exome or whole genome sequencing, pathogenic variants in the MAGEL2 gene were identified in all affected patients. All disease-causing sequence variants detected are predicted to result in a truncated protein, including one complex variant that comprised a deletion and inversion. Conclusions: Chitayat-Hall syndrome is caused by pathogenic variants in MAGEL2 and shares a common aetiology with the recently described Schaaf-Yang syndrome. The phenotype of MAGEL2 -related disorders is expanded to include growth hormone deficiency as an important and treatable complication.